Phosphotungstic acid‐enhanced microCT: Optimized protocols for embryonic and early postnatal mice. Issue 4 (28th November 2019) - Lesciotto, Kate M.; Motch Perrine, Susan M.; Kawasaki, Mizuho; Stecko, Timothy; Ryan, Timothy M.; Kawasaki, Kazuhiko; Richtsmeier, Joan T.
Abstract: Background: Given the need for descriptive and increasingly mechanistic morphological analyses, contrast‐enhanced microcomputed tomography (microCT) represents perhaps the best method for visualizing 3D biological soft tissues in situ. Although staining protocols using phosphotungstic acid (PTA) have been published with beautiful visualizations of soft tissue structures, these protocols are often aimed at highly specific research questions and are applicable to a limited set of model organisms, specimen ages, or tissue types. We provide detailed protocols for micro‐level visualization of soft tissue structures in mice at several embryonic and early postnatal ages using PTA‐enhanced microCT. Results: Our protocols produce microCT scans that enable visualization and quantitative analyses of whole organisms, individual tissues, and organ systems while preserving 3D morphology and relationships with surrounding structures, with minimal soft tissue shrinkage. Of particular note, both internal and external features of the murine heart, lungs, and liver, as well as embryonic cartilage, are captured at high resolution. Conclusion: These protocols have broad applicability to mouse models for a variety of diseases and conditions. Minor experimentation in the staining duration can expand this protocol to additional age groups, permitting ontogenetic studies of internal organs and soft tissue structures within their 3D in situ position. Key Findings: Visualization of embryonic soft tissue structures. Segmentation of embryonic soft tissues useful for 3D quantitative analysis. Expanded protocols for phosphotungstic acid‐enhanced microCT. Wax embedded protocol to reduce desiccation and improve microCT scan clarity.